Effects of Oat Complex High-Fiber Formula Powder on the Composition of Intestinal Microbiota and Enzyme Activities in Mice Induced by a High-Fat Diet - Huo, Rui; Zhang, Meili; Zhang, Yakun; Bai, Xue; Zhang, Yuanyuan; Guo, Xinyue (Frontiers in Nutrition, 2022)
Using oat-corn-konjac extruded mixed powder, oat bran micro powder, skim milk powder, Pueraria whole powder, and pumpkin powder as raw materials, a formula powder with high dietary fiber was prepared, and its effect on obesity in mice with a high-fat diet was investigated. After 7 days of adaptive feeding, the mice were divided into blank group, high-fat diet group, formula powder + high-fat diet group, and weight-loss drug + high-fat diet group. After 8 weeks of treatment, the body weight of mice were observed and measured to determine the composition of tract flora, liver leptin content, insulin content, and activities of AMP-activated protein kinase (AMPK), lipoprotein lipase (LPL), fatty acid synthetase (FAS), sterol-regulatory element-binding proteins (SREBPs), and acetyl CoA carboxylase 1 (ACC1). The results indicated that treatment with the formula powder could reduce the body weight of mice and increase the abundance of Bifidobacterium, Akkermansia, and Romboutsia compared to the group given a high-fat diet. Moreover, the leptin and insulin contents of the experimental group decreased from 5.67 μg/L to 0.12 μg/L and from 12.71 μg/L to 7.13 μg/L, respectively, compared to the control group, which was not significantly different from the blank group (P > 0.05). Also, the activities of AMPK and LPL increased, and the activities of FAS, SREBPs, and ACC1 were significantly decreased (P < 0.05). Some pathogenic bacteria were significantly positively correlated with leptin and FAS and significantly negatively correlated with LPL. Some beneficial bacteria were positively correlated with LPL. Therefore, the formula powder used in this study could reduce the body weight of mice, increase the abundance of some beneficial bacteria in the colonic intestinal microbiota, and improve the activities of enzymes related to lipid metabolism in the liver. This study provides a theoretical reference for the pathway by which high-fiber diet improves liver and intestinal metabolic abnormalities.